Glycol stabilized magnetic nanoparticles for photocatalytic degradation of xylenol orange. (23rd May 2018) - Ullah, Ikram; Ali, Farman; Ali, Zarshad; Humayun, Muhammad; wahab, Zain Ul
Abstract: In this work, we have successfully prepared ZnFe2 O4 magnetic nanoparticles as photocatalysts via co-precipitation method using triethylene glycol as a stabilizing agent. The resultant nanoparticles were annealed at 400 °C and then acid etched and surface functionalized with 3-(triethoxysilyl) propyl amine (APTES). Fourier transform infrared (FTIR) spectroscopy and x-ray diffraction (XRD) analysis were used to characterize these magnetic photocatalysts. XRD patterns revealed that the size of annealed and functionalized ZnFe2 O4 nanoparticles falls in the range of 23.3 and 13.9 nm, respectively. The optical band gaps of the magnetic photocatalysts were calculated from UV–Visible absorption spectra using Tauc plots. The band gap of the ZnFe2 O4 photocatalyst in acidic and basic medium was 2.47 and 2.7 eV, respectively. The performance of the magnetic photocatalysts was evaluated for xylenol orange (XO) degradation. The degradation rates of XO dye for the blank, annealed and functionalized photocatalysts at pH = 4 were 76%, 85%, and 90%, respectively. In addition, the influence of important parameters such as contact time, pH, catalyst, and dye dose were also investigated for all the three photocatalysts. The applied kinetics models demonstrated that the degradation followed pseudo 1st order.